Active Photoswitching of Sharp Fano Resonances in THz Metadevices. Issue 3 (14th November 2016) - Manjappa, Manukumara; Srivastava, Yogesh Kumar; Cong, Longqing; Al‐Naib, Ibraheem; Singh, Ranjan
Abstract : Fano resonances offer exciting features in enhancing the non‐linearity and sensing capabilities in metamaterial systems. An active photoswitching of Fano resonances in a terahertz metadevice at low optical pump powers is demonstrated, which signifies the extreme sensitivity of the high‐quality‐factor resonant electric field to the external light illumination.